Effect of body condition and season on yield and quality of in vitro produced bovine embryos. Issue 6 (26th November 2014) - Chrenek, Peter; Kubovičová, Elena; Olexíková, Lucia; Makarevich, Alexander V.; Toporcerová, Silvia; Ostró, Alexander
Summary: The aim of our study was to examine the effects of cow's body condition score (BCS; scale 1–5) and season on the quality of bovine in vitro produced embryos. The proportion of good quality oocytes (Q1 and Q2) was higher ( P < 0.05) in the BCS 2 (57.60%) and BCS 3 (60.90%) groups compared with the BCS 1 (43.60%) group. There were no statistical differences in embryo cleavage and blastocyst rate among the BCS groups. The highest total cell number (TCN, DAPI stain) of blastocysts ( P < 0.05), recorded in BCS 1 (122.27 ± 6.90) in comparison with BCS 2 (101.8 ± 3.60) or BCS 3 (105.44 ± 3.70) groups, was related to higher dead cell (DCI, TUNEL) index in this group (7.07%) when compared with BCS 2 (6.54%) or BCS 3 (6.06%), respectively. The yield of good quality oocytes during spring was lower ( P < 0.05) compared with the summer season. There were significant differences ( P < 0.05) in maturation and cleavage rates between autumn and summer (73.42%, 76.2% vs. 85.0%, 41.8%, respectively). The highest ( P < 0.01) blastocyst rate was noted during spring and summer months. Significant difference ( P < 0.05) in the TCN among spring (99.38 ± 3.90), autumn (110.1 ± 4.58) or summer (108.96 ± 3.52) was observed. The highest proportion of embryos with the best (grade I) actin cytoskeleton (phalloidin–TRITC) quality was noted during the summer months. Our results indicate that body condition affects the initial quality of oocytes, but does not affect embryo cleavage, blastocyst rate and actin quality. This finding may suggest that development in vitro can mask the influence of BCS. The season affects yield and quality of blastocysts in the way that the autumn period is more favorable for embryo development.